Follow-Up Comparison of Fluorescence Optical Imaging With Musculoskeletal Ultrasound for Early Detection of Psoriatic Arthritis - Büttner, Juliane; Glimm, Anne-Marie; Kokolakis, Georgios; Erdmann-Keding, Magdalena; Burmester, Gerd-Rüdiger; Hoff, Paula; Klotsche, Jens; Ohrndorf, Sarah (Frontiers in Medicine, 2022)
Early diagnosis of psoriatic arthritis (PsA) is crucial for patient outcome but hampered by heterogenous manifestation and lack of specific biomarkers. We recently showed that fluorescence optical imaging (FOI) can differentiate between patients with confirmed and suspected PsA. To follow-up patients with confirmed and suspected PsA focusing on patients with change from suspected to confirmed PsA by the use of FOI in comparison with musculoskeletal ultrasound (MSUS). Follow-up examination of patients included in the study performed by Erdmann-Keding et al. in which FOI of both hands was performed in a standardized manner using three predefined phases (p1-p3) and PrimaVistaMode (PVM). Comparison was drawn to grey-scale/power Doppler (GS/PD) MSUS of the clinically dominant hand (wrist, MCP, PIP, DIP 2–5) from dorsal/palmar. Patients with a change from suspected to diagnosed PsA showed an increased prevalence of joints with pathological enhancement in FOI (p=0.046) with an unchanged joint distribution pattern, especially with a dominant involvement of DIP joints. Compared to baseline, these patients were three times more common to show enhancement in FOI p3 at follow-up. Newly detected pathologic joints by FOI (PVM, p2) and MSUS at follow-up were positively associated with the change of diagnosis from suspected to confirmed PsA (FOI: AUC 0.78; GSUS: AUC 0.77). FOI appears to be a helpful tool to detect early PsA and to distinguish between acute and chronic disease stages. It could thereby become a suitable tool as screening method to select psoriasis patients with indication for further rheumatological evaluation.